Fundamental Drill#5

Algebra Level 4

Let f ( x ) = x 2 + 3 x 4 f(x)=x^2+3x-4 and g ( x ) = x 2 4 x + 4 g(x)=x^2-4x+4 .

If h ( x ) = f ( x ) + α g ( x ) h(x)=f(x)+\alpha g(x) , where α = m n \alpha = \dfrac mn with m m and n n being positive coprime integers, and h ( x ) = p ( x q ) 2 h(x)=p(x-q)^2 for some rational numbers p p and q q .

Find m + n m+n .

Try more of my fundamental problems here .


The answer is 49.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jun 24, 2018

Given that { f ( x ) = x 2 + 3 x 4 = ( x 1 ) ( x + 4 ) g ( x ) = x 2 4 x + 4 = ( x 2 ) 2 \begin{cases} f(x) = x^2+3x-4 = (x-1)(x+4) \\ g(x) = x^2-4x+4 = (x-2)^2 \end{cases}

h ( x ) = f ( x ) + α g ( x ) = ( x 1 ) ( x + 4 ) + α ( x 2 ) 2 = p ( x q ) 2 \implies h(x) = f(x) + \alpha g(x) = (x-1)(x+4) + \alpha (x-2)^2 = p(x-q)^2

Then we have

h ( 1 ) = 0 + α = p ( 1 q ) 2 . . . ( 1 ) h ( 4 ) = 0 + 36 α = p ( 4 q ) 2 . . . ( 2 ) h ( 2 ) = 6 = p ( 2 q ) 2 . . . ( 3 ) \begin{aligned} h(1) & = 0 + \alpha = p(1-q)^2 & ...(1) \\ h(-4) & = 0 + 36\alpha = p(-4-q)^2 & ...(2) \\ h(2) & = 6 = p(2-q)^2 & ...(3) \end{aligned}

( 2 ) ( 1 ) : ( 4 + q ) 2 ( 1 = q ) 2 = 36 4 + q 1 q = 6 4 + q = 6 6 q q = 2 7 \begin{aligned} \frac {(2)}{(1)}: \quad \frac {(4+q)^2}{(1=q)^2} & = 36 \\ \frac {4+q}{1-q} & = 6 \\ 4+q & = 6 - 6q \\ \implies q & = \frac 27 \end{aligned}

( 3 ) : p ( 2 2 7 ) 2 = 6 p = 49 24 \begin{aligned} (3): \quad p\left(2-\frac 27\right)^2 & = 6 \\ \implies p & = \frac {49}{24} \end{aligned}

( 1 ) : α = 49 24 ( 1 2 7 ) 2 = 25 24 \begin{aligned} (1): \quad \alpha & = \frac {49}{24}\left(1-\frac 27\right)^2 = \frac {25}{24} \end{aligned}

Therefore, m + n = 25 + 24 = 49 m+n=25+24= \boxed{49} .

@Chew-Seong Cheong Nice solution!

donglin loo - 2 years, 11 months ago

Log in to reply

Glad that you like it.

Chew-Seong Cheong - 2 years, 11 months ago
Donglin Loo
Jun 22, 2018

Relevant wiki: Quadratic Discriminant

f ( x ) = x 2 + 3 x 4 f(x)=x^2+3x-4

g ( x ) = x 2 4 x + 4 g(x)=x^2-4x+4

h ( x ) = f ( x ) + α g ( x ) = x 2 + 3 x 4 + α ( x 2 4 x + 4 ) = ( 1 + α ) x 2 + ( 3 4 α ) x + ( 4 α 4 ) h(x)=f(x)+\alpha g(x)=x^2+3x-4+\alpha(x^2-4x+4)=(1+\alpha)x^2+(3-4\alpha)x+(4\alpha-4)

When h ( x ) = 0 h(x)=0

p ( x q ) 2 = 0 p(x-q)^2=0

x = q x=q

There is one real root only.

Or in other words, there are two equal real roots.

When h ( x ) = 0 ( 1 + α ) x 2 + ( 3 4 α ) x + ( 4 α 4 ) = 0 h(x)=0 \Rightarrow (1+\alpha)x^2+(3-4\alpha)x+(4\alpha-4)=0

Discriminant = ( 3 4 α ) 2 4 ( 1 + α ) ( 4 α 4 ) = 0 =(3-4\alpha)^2-4(1+\alpha)(4\alpha-4)=0

9 24 α + 16 α 2 16 ( α + 1 ) ( α 1 ) = 0 9-24\alpha+16\alpha^2-16(\alpha+1)(\alpha-1)=0

9 24 α + 16 α 2 16 ( α 2 1 ) = 0 9-24\alpha+16\alpha^2-16(\alpha^2-1)=0

9 24 α + 16 = 0 9-24\alpha+16=0

24 α = 25 24\alpha=25

α = 25 24 \alpha=\cfrac{25}{24}

p + q = 25 + 24 = 49 p+q=25+24=49

Alternative approach: \textbf{Alternative approach:} You can solve this too by completing the square as the quadratic formula is derived using completing the square method.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...